Recent Advances in Asymmetric [1,2]-Stevens-Type Rearrangement via Metal Carbenes - Shi, Chong-Yang; Zhou, Bo; Teng, Ming-Yu; Ye, Long-Wu (Synthesis, 2023)
The [1,2]-Stevens rearrangement is a widely used transformation in synthetic organic chemistry. However, enantioselective versions are relatively limited and most of them rely on substrate-induced methodologies. In recent years, metal carbene chemistry has been extensively investigated, and the related asymmetric [1,2]-Stevens rearrangement has experienced rapid development by employing ylide intermediates generated from the reaction of metal carbenes with heteroatoms. This review summarizes recent advances in the asymmetric [1,2]-Stevens-type rearrangement via metal carbenes by presenting their product diversity, selectivity, and mechanistic rationale, which is organized based on the mode of chirality control.1 Introduction2 Substrate-Induced Asymmetric [1,2]-Stevens-Type Rearrangement3 Catalyst-Controlled Asymmetric [1,2]-Stevens-Type Rearrangement4 Conclusion and Outlook
Keywords: [1,2]-Stevens rearrangement; metal carbenes; substrate-induced; asymmetric catalysis